Case Report: Ofatumumab treatment in a patient with rituximab-intolerant refractory autoimmune GFAP astrocytopathy - Cao, Shugang; Du, Jing; Pan, Sidi; Zhang, Juanjuan; Xu, Si; Wei, Ling; Tian, Yanghua (Frontiers in Immunology, 2023)
Background Ofatumumab, a fully humanized anti-CD20 monoclonal antibody, has shown promising efficacy in limited cases of neuromyelitis optica spectrum disorder, but there is a lack of studies on its use in autoimmune glial fibrillary acidic protein (GFAP) astrocytopathy. We present a case of refractory GFAP astrocytopathy with poor response to conventional immunosuppressants and rituximab who responded well to subcutaneous ofatumumab. Case report The patient is a 36-year-old woman with a diagnosis of GFAP astrocytopathy and high disease activity. She experienced five relapses over three years despite immunosuppressive treatment with oral prednisone, azathioprine, mycophenolate mofetil, and intravenous rituximab. Additionally, her circulating B cells were not completely depleted during the second administration of rituximab and an allergic reaction occurred. Based on insufficient B cell depletion and allergic reaction to rituximab, subcutaneous ofatumumab was introduced. After twelve injections of ofatumumab without injection-related reactions, she had no further relapses and was sufficiently depleted of the circulating B cells. Discussion This case illustrates the effective use and good tolerance of ofatumumab in GFAP astrocytopathy. Further studies are needed to investigate the efficacy and safety of ofatumumab in refractory GFAP astrocytopathy or those intolerant to rituximab.